PENETAPAN KADAR VITAMIN C SECARA IODIMETRI PADA TOMAT CHERRY KUNING (Solanum lycopersicum Var. Cerasiforme) YANG DIBUDIDAYAKAN SECARA HIDROPONIK - Fitri, Widya; Manurung, Kesaktian; Gustiani Tarigan, Yenni (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Vitamin C is a vitamin that is necessary for a healthy body. Vitamin C is one of the water-soluble vitamins and has a strong reducing power. This reducing power of vitamin C is the reason for choosing the method of determining its levels by iodimetry. The purpose of this study was to determine the levels of vitamin C contained in Yellow Cherry Tomatoes (Solanum lycopersicum Var. Cerasiforme) which were hydroponically cultivated and those grown in soil were carried out by iodimetry.This method uses a descriptive method, namely to examine the levels of Vitamin C samples contained in Yellow Cherry Tomatoes (Solanum lycopersicum Var. Cerasiforme) which are cultivated hydroponically and planted in the ground.Based on the results of the analysis carried out by iodimetric titration, the average level of vitamin C in Yellow Cherry Tomatoes cultivated hydroponically was 29,55 ± 1,2854 mg/100 g and the average level in Yellow Cherry Tomatoes grown in soil was 25,09 ± 1,2862 mg/100 g. Based on these results, it can be concluded that the levels of vitamin C in Yellow Cherry Tomatoes that are cultivated hydroponically are higher than the levels of vitamin C grown in the soil due to different growth factors and plant nutrients.